Connexin 43 gene therapy prevents persistent atrial fibrillation in a porcine model - Bikou, Olympia; Thomas, Dierk; Trappe, Kerstin; Lugenbiel, Patrick; Kelemen, Kamilla; Koch, Martin Christoph; Soucek, Radim; Voss, Frederik; Becker, Rüdiger; Katus, Hugo; Bauer, Alexander (Cardiovascular research, 2011)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, and effective treatment of AF still remains an unmet medical need. AF is associated with atrial conduction disturbances caused by electrical and/or structural remodelling. We hypothesized that AF suppresses expression of the gap junction protein connexin (Cx) 43 and that Cx43 gene transfer to both atria would prevent persistent AF. The first aim of this study was to assess whether AF is associated with connexin remodelling in a porcine model. A strategy to suppress persistent AF by gene therapy was then developed and evaluated in vivo.AF was induced in domestic pigs via atrial burst pacing, causing a 62.4% reduction in atrial Cx43 protein. Adenoviruses encoding for Cx43 (AdCx43) or green fluorescent protein (AdGFP) were injected into both atria, followed by epicardial electroporation to enhance transgene expression. Combining direct injection of adenoviruses with electroporation achieved GFP reporter gene expression in ∼50% of atrial cells in vivo. AdCx43-treated animals exhibited a 2.5-fold increase in atrial Cx43 protein content and did not develop persistent AF during the observation period of 14 days. In contrast, control animals developed persistent AF within 7.4 ± 0.5 days. Rapid ventricular heart rates during AF led to deterioration of cardiac function in control pigs but not in pigs treated with AdCx43.Our results highlight the contribution of Cx43 to the pathophysiology of AF and demonstrate the viability of gene therapy for prevention of atrial arrhythmias.